Dehydration of wolfberry fruit using pulsed vacuum drying combined with carboxymethyl cellulose coating pretreatment. (December 2020) - Yu, Fen; Li, Yuanhui; Wu, Zhenfeng; Wang, Xuecheng; Wan, Na; Yang, Ming
Abstract: Drying is one of the oldest and most important food preservation techniques but requires promotion to maintain the quality of products. In this paper, pulsed vacuum drying (PVD) combined with carboxymethyl cellulose (CMC) coating pretreatment was employed as a new approach to improve the drying efficiency and produce dried wolfberry with acceptable quality. To achieve these goals, its influence on drying characteristics, energy consumption, drying shrinkage, color, total polysaccharide content and total polyphenol content in dried wolfberry fruit were comparatively evaluated with PVD and convective drying with hot air (CDHA). The results showed that PVD combined with CMC coating pretreatment allowed significantly higher drying efficiency, lower energy consumption, less drying shrinkage and better preservation of color, total polysaccharide content and total polyphenol content in wolfberry fruit (p ≤ 0.05). Increasing CMC concentration from 0.5% to 3.0% (w/w) resulted in an improved drying efficiency and product quality, and reduced energy consumption, the optimal CMC concentration was 2.0% (w/w). Overall, PVD combined with CMC coating pretreatment could be considered as an effective approach to improve the quality of the dried wolfberry fruit and reduce energy consumption. Highlights: Pulsed vacuum drying combined with CMC coating pretreatment was proposed to dry wolfberry fruit. The effect of drying conditions on drying characteristics and qualities was investigated. The proposed method improved the drying efficiency and product quality.